2021
DOI: 10.3389/fped.2021.564991
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment With Intrathecal and Intravenous Polymyxin B-Based Combination Against MDR Acinetobacter baumannii Meningitis in Pediatric Patient: A Case Report

Abstract: Background: Nosocomial meningitis with multidrug-resistant (MDR) or extensively drug-resistant (XDR) Acinetobacter baumannii is a life-threatening complication in neurosurgery. Treatment of these infections is challenging because of poor penetration of the available antibiotics into the cerebrospinal fluid (CSF). Intrathecal (ITH) or intraventricular (IVT) administration of antibiotics is increasingly used as the last treatment option against MDR/XDR Gram-negative bacteria meningitis not responding to intraven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“… 34 Therefore, it can be seen that polymyxin B is relatively safe. In addition, there are other small sample studies that have confirmed the same efficacy of polymyxin B 35–40 ( Table 3 ). In most cases, craniocerebral trauma and cerebral hemorrhage are common primary diseases.…”
Section: Discussionmentioning
confidence: 91%
“… 34 Therefore, it can be seen that polymyxin B is relatively safe. In addition, there are other small sample studies that have confirmed the same efficacy of polymyxin B 35–40 ( Table 3 ). In most cases, craniocerebral trauma and cerebral hemorrhage are common primary diseases.…”
Section: Discussionmentioning
confidence: 91%
“…The neonate received intraventricular polymyxin B at 40,000 units per dose for 14 doses. 16 Xing H 18 selected 50,000 U once per day for the first 4 days, then 50,000 U once every other day. Another boy in early childhood received 5mg once per day.…”
Section: Discussionmentioning
confidence: 99%
“…Common adverse effects include nephrotoxicity, neurotoxicity, and pigmentation of the skin (polymyxin B sulfate only). Several studies have shown the efficacy of intravenous infusions of CMS or PBS and intraventricular/intrathecal injections in the treatment of NCNSIs [4][5][6]. CS (from Shanghai New Asia Pharmaceuticals, Shanghai, China) was approved for clinical use by the Chinese National Medical Products Administration on 16 April 2018 [7], and has rarely been reported in its clinical application.…”
Section: Introductionmentioning
confidence: 99%